Entrepreneurial Innovations in Countries at Different Stages of Development - Éva Komlósi; Balázs Páger; Gábor Márkus (Foresight and STI Governance)
The aim of our paper is to provide a comprehensive picture of the role of innovation within the entrepreneurial ecosystem in certain countries. In this way, we propose the following research question as to what kind of interrelatedness can be observed between the innovation capability of a country and other elements of its entrepreneurial ecosystem. Ninety-five countries have been involved in our analysis, which initially have been grouped by their level of economic development and a group of transition countries has been created as well. In order to measure these relations, the Global Entrepreneurship Index (GEI) was applied. This index measures the qualitative aspects of the entrepreneurial ecosystem in a national context. The index consists of fourteen pillars covering the relevant aspects of the entrepreneurial ecosystem. Out of the pillars, there are three pillars associated with three different aspects of innovation: Technology Absorption, Product Innovation, and Process Innovation. After analyzing the pillars, we conducted a k-means cluster analysis in order to demonstrate whether countries with the same level of development are ranked in a common group if they are clustered by the values of the three innovation pillars. Our results suggest that the quality of the entrepreneurial ecosystem reflects the level of economic development. Regarding the role of innovation, it seems that the innovation-related pillars have an important role within the entrepreneurial ecosystem. Technology Absorption is highly related to the GEI score and the level of economic development since the most developed countries have the highest values for this pillar. While the Product and Process Innovation pillars have a relatively strong relationship with GEI score as well, it seems that a couple of countries have higher pillar values in these innovation-related pillars than the position of their GEI scores would lead one to expect. This may indicate that these countries have relatively good performance in research and development, but other components of their entrepreneurial ecosystem may hamper the exploitation of the results achieved by new firms.